Driving Towards Highly Selective and Coking‐Resistant Natural Gas Reforming Through a Hybrid Oxygen Carrier Design. Issue 2 (6th November 2020) - Qin, Lang; Chen, Yu‐Yen; Guo, Mengqing; Liu, Yan; A. Fan, Jonathan; Fan, Liang‐Shih
Abstract: Carbon deposition can be promoted by catalyst‐assisted C−H bond dissociation, which is one of the most concerning issues in reaction engineering. Treatment of carbon contamination inevitably generates CO2 which has a detrimental effect on the environment. Consequently, the development of efficient oxygen carriers is important to commercial viability of chemical looping processes. In this work, density functional theory (DFT) calculations were conducted and reveal that carbon deposition is a cascade reaction of accumulative C−C bond forming that deactivates LFO surface due to gradual accumulation of lattice oxygen vacancies. Guided by DFT mechanistic predictions, we tailor catalytic reactive perovskite LaFeO3 (LFO) with high oxygen carrying hematite Fe2 O3 (FO) into a hybrid oxygen carrier LFO‐FO. The LFO‐FO oxygen carrier exhibits excellent carbon inhibition capability and high reactivity with syngas selectivity above 98 %. This work proposes a promising strategy toward oxygen carrier development with low cost, high reactivity, and selectivity for chemical looping technology. Abstract : Chemical looping processes : Oxygen vacancy‐induced carbon deposition occurs as cascade reactions on oxygen‐deficient surfaces in many hydrocarbon conversion systems unavoidably. Guided by atomistic modelling, a hybrid oxygen carrier with catalytic LaFeO3 (LFO) and oxygen carrying Fe2 O3 (FO) was developed. The hybrid oxygen carrier exhibits excellent reactivity, recyclability and carbon inhibition capability in cyclic redox scheme. This work proposes a promising strategy toward oxygen carrier development with low cost, high reactivity, and selectivity for chemical looping technology.